Development of Android Based Game „Weiβt du das?“ for German Vocabulary Learning - Asyananda Dila Putriningtias; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
This research and development aim to develop games based on android “Weiβt du das?” for vocabulary learning on the Wohnung theme. The research and development  model used in this research and development is the ADDIE, which consists of five stages. The stages are: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The data of this study were obtained from open questionnaire sheets of product trials by media and material experts. The result showed that game product could be used for learning vocabulary on the Wohnung theme.